Vulnerability of refugees with communication disabilities to SGBV: evidence from Rwanda - Marshall, J; Barrett, H; Ebengo, A (Refugee Studies Centre, University of Oxford, 2017)
Refugees with communication disabilities are particularly vulnerable to sexual and gender-based violence, in part because of their limited ability to report abuse.